Expert System for Troubleshooting A Local Area Network (LAN) - Reyna-González, Julissa Elizabeth; Villavicencio Cabrera, Marco Antonio; Ojeda, Víctor Pedro Cuadros; Anaí Fernández-Otoya, Dra. Fiorela; Céspedes Aguirre, Dra. Lourdes Lucila (International Journal of Intelligent Systems and Applications in Engineering, 2023)
The present research work called "EXPERT SYSTEM TO DIAGNOSE AND PROPOSE THE SOLUTION OF FAILURES IN A LOCAL AREA NETWORK OF THE SECURITY AND NETWORK MANAGEMENT CENTER" will allow the development of a prototype of an expert system that will help to propose the immediate solution to failures at the level of connectivity hardware, interface hardware, communication software, and user failures in the LAN. This information was provided to us by the owner of the company where all network improvement activities will take place. In this research work, surveys were carried out aimed at network technical personnel and users with basic knowledge of computing and telecommunications who work in the company at the Network Security and Management Center in order to diagnose failures in the LAN network and propose an expert system. Network specialists were consulted, questioned and interviewed and information was obtained that later allowed the knowledge to be processed in natural language, to then formulate the production and reasoning rules of the process using the java programming language for the design of the prototype that was finally submitted. to a simulation of tests on some computer equipment, as well as the development of an explanatory module, so that anyone with basic knowledge of networks and communications can use it.